Does polyomavirus infection interfere with bladder cancer fluorescence in situ hybridization?. Issue 3 (5th September 2013) - Hossain, Deloar; Hull, David; Kalantarpour, Fatemeh; Maitlen, Rebecca; Qian, Junqi; Bostwick, David G.
<x xml:space="preserve">Abstract</x> Urine cytology is a proven and widely used screening tool for the detection of urothelial carcinoma. However, morphologic features of polyomavirus infected cells, characterized by nuclear inclusions (decoy cells) are a known source of diagnostic confusion with malignancy. Fluorescence in situ hybridization (FISH) is now routinely used to support the cytological diagnosis of urothelial carcinoma and monitor for recurrence. We sought to determine whether polyomavirus infection could result in positive FISH results (aneuploidy). This study deals with retrospective study of 100 polyomavirus‐infected urine samples from patients with no history of urothelial carcinoma or organ transplantation. All cases were stained with Papanicolaou and acid hematoxylin stain. One slide from each sample was de‐stained and FISH was performed using chromosome enumeration probes 3, 7, 17, and locus‐specific probe 9p21. Adequate cells for FISH analysis (25 cells) were present in 81 cases; 19 cases were insufficient due to loss of cells during de‐staining and FISH preparation process. All polyomavirus‐infected cells (decoy cells) exhibited a normal chromosome pattern. Four cases were FISH positive, but there were no positive decoy cells. Decoy cells did not exhibit aneuploidy by FISH. The presence of decoy cells does not exclude the possibility of concurrent urothelial carcinoma. Acid hematoxylin stain appeared to supplement the Papanicolou stain in identifying and confirming the presence of polyomavirus infection. Diagn. Cytopathol. 2014;42:225–229. © 2013 Wiley Periodicals, Inc.